Review of the Book The Detailed Register of the Tabriz Liva (1728) (translation, commentary, and introduction by Academician Shahin Mustafayev). – Baku: Baku State University Press, 2024. – In two volumes. Vol. 1: 544 p.; Vol. 2: 392 p. - Gezalova, Nigar Rovsan gyzy (History, Archeology and Ethnography of the Caucasus, 2025)
Abstract. Ottoman tax registers are fundamental sources for studying the socio-economic history, administrative structure, and demographic composition of the Ottoman Empire. However, their complexity significantly limits researchers’ access to these documents. Written in Ottoman Turkish using Arabic script, they require not only advanced linguistic proficiency but also a deep understanding of bureaucratic terminology, taxation structures, and the imperial administrative system.In this context, the two-volume edition The Detailed Register of the Tabriz Liva, prepared by Academician Shahin Mustafayev, constitutes a significant contribution to the study of the socio-economic history of the Safavid state in the early 18th century. The work is based on the critical edition of the 1728 Ottoman tax register of the Tabriz Liva. Mustafayev not only translated the document into Azerbaijani but also meticulously deciphered, annotated, and comprehensively analyzed it, thereby making it accessible to the academic community. The source provides insights into the distribution of tax burdens across different social groups, the dynamics of taxation depending on landownership types, and the economic activity of the Tabriz Liva population.This reviewed edition serves as an exemplary scholarly publication of a historical source, combining an accurate translation with extensive commentary and rigorous academic analysis. The introduction of this register into academic discourse significantly enhances our understanding of the taxation system and administrative governance of the Ottoman Empire in Azerbaijan and Iran. This study is of particular interest to specialists in Ottoman and Iranian studies, as well as historians examining the socio-economic development of the region in the early modern period.
Keywords: Ottoman tax registers; Tabriz liva; administrative governance; socio-economic history; Ottoman-Safavid wars; ethno-demographic structure.